Challenges in Implementing Digital-Based Employee Recruitment and Selection in the Personnel and Human Resource Development Agency (BKPSDM) of North Nias Regency - Aditya Waruwu; Delipiter Lase; Meiman Hidayat Waruwu; Yamolala Zega (ProBisnis : Jurnal Manajemen, 2025)
This study examines the challenges faced in the implementation of digital-based recruitment and selection for the State Civil Apparatus (ASN) at the Human Resources Development and Personnel Agency (BKPSDM) of North Nias Regency. The transition from manual procedures to the SSCASN digital platform aims to improve transparency, efficiency, and accuracy in public-sector recruitment. However, digital transformation in an island-based region presents several obstacles. This qualitative research adopts a descriptive approach, collecting data through in-depth interviews, observation, and documentation involving BKPSDM officials, system operators, and applicants. The findings reveal that digital recruitment has enhanced accountability, reduced administrative errors, and improved information accessibility. Nonetheless, major challenges persist, including unstable internet connectivity, limited technological infrastructure, inadequate digital competencies among staff and applicants, system errors during peak registration periods, and gaps in data validation between online and manual documents. These challenges affect the smoothness of the recruitment cycle and require strategic interventions. The study concludes that although digital recruitment strengthens governance and meritocracy, its success depends on improving infrastructure, enhancing human resource capacities, and strengthening technical support systems. Recommendations include capacity-building programs, system refinement, and multi-stakeholder collaboration to ensure sustainable digital transformation.